2011
DOI: 10.1007/s00148-011-0390-8
|View full text |Cite
|
Sign up to set email alerts
|

The individual cost of sick leave

Abstract: This paper aims to estimate the causal effect of sick leave on subsequent earnings and employment, using an administrative dataset for Norway. To obtain experiment-like variation in sick leave among otherwise similar workers, the leniency of these workers' physicians-certifying sickness absences-is used as an instrumental variable for sick leave. A 1 percentage point increase in a worker's sick leave rate is found to reduce his earnings by 1.2% 2 years later. Around half of the reduction in earnings can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 17 publications
2
52
0
5
Order By: Relevance
“…Det kan likevel ikke utelukkes at sykefravaer mer indirekte har betydning for hvordan arbeidstakere blir vurdert og behandlet både når det gjelder oppsigelser og for eksempel ved lønnsfastsettelse eller opprykk til høyere stillinger. Undersøkelser tyder på at høyt fravaer kan føre til dårligere lønnsutvikling, dog uten at de spesifikke mekanismene som gir dette resultatet er klarlagt (se for eksempel Markussen 2012). Frykt for slike negative konsekvenser kan føre til at arbeidstakere har lavere sykefravaer enn de ellers ville ha hatt.…”
Section: Hva Kan Forklare Høyere Sykefravaer I Offentlig Sektor?unclassified
“…Det kan likevel ikke utelukkes at sykefravaer mer indirekte har betydning for hvordan arbeidstakere blir vurdert og behandlet både når det gjelder oppsigelser og for eksempel ved lønnsfastsettelse eller opprykk til høyere stillinger. Undersøkelser tyder på at høyt fravaer kan føre til dårligere lønnsutvikling, dog uten at de spesifikke mekanismene som gir dette resultatet er klarlagt (se for eksempel Markussen 2012). Frykt for slike negative konsekvenser kan føre til at arbeidstakere har lavere sykefravaer enn de ellers ville ha hatt.…”
Section: Hva Kan Forklare Høyere Sykefravaer I Offentlig Sektor?unclassified
“…Hence, the functional relationship q(d) reflects the negative impact of absence on future (expected) income, for which there is also substantial empirical evidence (see Hansen 2000, Hesselius 2007, Henningsen and Haegeland 2008, Andersen 2010, and Markussen 2012.…”
Section: Foundationsmentioning
confidence: 99%
“…Similarly, Markussen (2012) has shown that sick leave has a negative effect on subsequent earnings and employment.…”
Section: Literature Reviewmentioning
confidence: 98%